PAHAM KEAGAMAAN DOSEN PAI UNIVERSITAS PASUNDAN BANDUNG - Suprapto Suprapto (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2014)
Religious understanding of Islamic studies lecturers in Pasundan University Bandung in this study is related to the relation between religion and state, relation between religion and tolerance, relation between religion and human rights, and relation between religion and gender equality. The findings include that the state should be involved in religious affairs in order to create order to avoid disharmony in inter-religious relations. The state has the authority to conduct enforcement in case of problems related to inter-religious relations. The conception of human rights in Islam is balance between rights and obligations. With regard to gender equality, there is atendency that leadership in politics or government must be held by men, not women because men are destined to become the leader on earth. Nevertheless, the informants believe that women can be made leaders if there is no man who is able to become a leader.